2002
DOI: 10.1128/aem.68.4.2066-2070.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and Magnetic Material on Immunomagnetic Separation of Cryptosporidium Oocysts from Concentrated Water Samples

Abstract: In this study, we examined the effect that magnetic materials and pH have on the recoveries of Cryptosporidium oocysts by immunomagnetic separation (IMS). We determined that particles that were concentrated on a magnet during bead separation have no influence on oocyst recovery; however, removal of these particles did influence pH values. The optimal pH of the IMS was determined to be 7.0. The numbers of oocysts recovered from deionized water at pH 7.0 were 26.3% higher than those recovered from samples that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
2
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 6 publications
0
21
2
7
Order By: Relevance
“…Although previous research indicated that IMS efficiencies can be affected by water quality parameters such as pH (14) and iron content (24), no specific water quality parameter was found to correlate with IMS efficiency data in this study. IMS was found to provide consistently high recovery performances for C. parvum (90 to 100%).…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Although previous research indicated that IMS efficiencies can be affected by water quality parameters such as pH (14) and iron content (24), no specific water quality parameter was found to correlate with IMS efficiency data in this study. IMS was found to provide consistently high recovery performances for C. parvum (90 to 100%).…”
Section: Discussioncontrasting
confidence: 42%
“…It has been shown in previous studies that the performance effectiveness of immunological techniques (e.g., immunomagnetic separation-immunofluorescent-antibody staining [IMS-IFA staining]) (14,24) and molecular assays (e.g., PCR and reverse transcription-PCR [RT-PCR]) (1,11) can be negatively affected by various water quality conditions (e.g., pH, iron content, or organic compounds), although relatively few studies of analytical method inhibition have focused on drinking water. Because detection of Cryptosporidium and Giardia is important for water quality monitoring, understanding the effects of water quality on available IMS techniques for these microbes, such as those incorporated into USEPA Method 1623 (22), is critical.…”
mentioning
confidence: 99%
“…Many investigators found that turbidity was related to recoveries of oocysts (4,5,7,15,26). The efficiency of the IMS technique was shown to decrease when the adjusted pH deviated from 7.0 (16) or when dissolved iron concentrations were greater than 4 mg/liter (38). In contrast, in the Information Collection Rule Supplemental Survey (ICRSS), wherein 430 samples were collected from 87 source waters, all measured water quality properties, including turbidity, were found to be unrelated or weakly related to recoveries of oocysts (32).…”
mentioning
confidence: 99%
“…Although cryptosporidiosis is mainly confined to young individuals, low-level asymptomatic infections in postweaned and adult cattle have been reported (6), with up to 10 4 oocysts per g of feces excreted (17). In addition, postparturient ewes may shed increased but low concentrations of C. parvum oocysts (100 to 5,700 oocysts g Ϫ1 ) (21).…”
mentioning
confidence: 99%
“…However, an attempt to improve recovery by using EDTA to sequester metal ions that may compete for bead binding sites was unsuccessful. Recent studies have demonstrated that the pH during oocyst capture is an important factor that affects the recovery of oocysts by IMS (10) and that the levels of recovery of oocysts from deionized water at pH 7.0 were significantly higher than those from water that deviated as little as 0.12 pH unit from the optimum. In the present study, deviation of the pH from the optimum during the IMS procedure was not considered to be the cause of poor recovery of oocysts from pig feces, since when it was checked, the pH before and after IMS deviated little from the optimum (data not shown).…”
mentioning
confidence: 99%